Patency of Posterior Circulation Branches Covered by Flow Diverter Device: A Hemodynamic Study - Wu, Xinzhi; Tian, Zhongbin; Liu, Jian; Zhang, Yisen; Li, Wenqiang; Zhang, Ying; Chen, Junfan; Zhou, Yangyang; Yang, Xinjian; Mu, Shiqing (Frontiers in Neurology, 2019)
Objective: Flow diverter devices are increasingly used in the treatment of posterior circulation aneurysms, sometimes necessarily involving ostia of side branches and perforators. The aim of this study was to identify the hemodynamic influence of flow diverters on side branches and perforators of the posterior circulation. Methods: We performed a retrospective study of consecutive patients treated by a flow diverter device for posterior circulation aneurysms with anterior inferior cerebellar artery (AICA) or posterior inferior cerebellar artery (PICA) involvement. Computational fluid dynamics (CFD) were used to discern hemodynamic changes of branches after deployment of the flow diverter. Results: We studied 18 branches from 17 patients (mean age, 50.72 ± 8.17 years). No branches were occluded on immediate angiography and later follow-up. Average flow velocity in aneurysms decreased from 0.077 ± 0.065 m/s to 0.025 ± 0.025 m/s (p < 0.01). Average flow velocity in branch ostia decreased from 0.29 ± 0.14 m/s to 0.27 ± 0.16 m/s (p = 0.189). The difference in flow velocity reduction ratio between aneurysms and branches was statistically significant (68.8 vs. 9.5%; p < 0.001). The mean pressure in branch ostia increased from 10,717.4 ± 489.0 to 10,859.0 ± 643.4 Pa (p < 0.01). Conclusion: While a flow diverter device is capable of slowing down aneurysmal inflow, it is unable to block the flow into branches and perforators when used in the treatment of posterior circulation aneurysms; flow velocity in branches even increased in some cases. With a low branch occlusion ratio, it may be acceptable to cover posterior circulation branches and perforators if unavoidable.